Evaluation of antimicrobial and antioxidant activity of Halia Merah (Zingiber officinale var. rubrum Theilade) ethanolic extract obtained from Desa Wisata Tuo Pariangan, West Sumatra - Shaharin, Muhammad Syazani; Arief Putra, Aronal; Sandra, Afriani; Aani, Siti Nur Anisah; Md Yasin, Ida Muryany (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Halia Merah (Zingiber officinale var. rubrum Theilade) is serve as a good source of antioxidants and very useful in medicine field especially in area where it is native such as West Sumatra, Indonesia. This study of antimicrobial and antioxidant activity aims to determine the antimicrobial activity of Halia Merah ethanolic extract using disc diffusion assay and to evaluate the antioxidant activity of Halia Merah in scavenging free radicals. The concentration of Halia Merah ethanolic extract ranging from 50 mg/mL, 100 mg/mL, 200 mg/mL and 400 mg/mL. Based on the result obtained, the highest concentration that is 400 mg/mL showed the largest inhibition zones. The result was 10.00±0.00 mm for S. aureus, 28.50±1.06 mm for B. subtilis, 9.50±1.50 mm for P. aeruginosa and 22.75±1.75 mm for E. coli. The antioxidant activity that was measured by using DPPH Radical Scavenging Assay determined that the Halia Merah ethanolic extract scavenging activity increased when the concentration is increased; (80.50% at 50 mg/mL, 88.59% at 100 mg/mL, 91.70% at 200 mg/mL, and 96.27% at 400 mg/mL). By using ANOVA analysis, it indicated that There were significant differences among different concentration used (p<0.05). As conclusion, the different concentrations of Halia Merah ethanolic extracts have the ability inhibiting the growth of bacteria from Gram-positive and Gram-negative bacteria. Halia Merah ethanolic extract also showed a positive activity of antioxidant by using DPPH Radical Scavenging Assay. In addition, there were also a high possibility that Halia Merah could be used as an alternative for a prescription and medicine, act as a traditional medicine with a greater cure rate compared to commercial antibiotics and antioxidant.